Dynamic unawareness and rationalizable behavior - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2009)
We define generalized extensive-form games which allow for mutual unawareness of actions. We extend Pearce's (1984) notion of extensive-form (correlated) rationalizability to this setting, explore its properties and prove existence. We define also a new variant of this solution concept, prudent rationalizability, which refines the set of outcomes induced by extensive-form rationalizable strategies. Finally, we define the normal form of a generalized extensive-form game, and characterize in it extensive-form rationalizability by iterative conditional dominance.
Keywords: C70; C72; D80; D82; 330; unawareness; extensive-form games; extensive-form rationalizability; prudent rationalizability; iterative conditional dominance